Long-term karyological study of RVP3 tumour cells grown in vitro - Sainerová, H; Svoboda, J (Folia biologica, 1978)
The RVP3 cell line established from an in vivo passaged RVP3 tumour, which originally arose in RSV-injected mice, was analyzed at different passage levels and characterized virologically and cytogenetically. The RVP3 cell line is characterized by the presence of 2 to 5 medium-sized to large metacentric chromosomes, the majority of the mitoses contain about 1 subtelocentric chromosome, and in addition, every mitosis contains several chromosomal structures corresponding to the group called m-ms that comprises both minute chromatin bodies and microchromosomes. In three monocellular clones derived from the RVP3 cell line with a similar karyological picture it was established that the number of m-ms increased proportionally to the total number of chromosomes in individual metaphases. It was verified that: the RVP3 cell population does not contain any transmissible agent producing chromosomal changes in mouse cells; RVP3 cells are highly malignant; no RSV could be rescued from the clone tested. The significance of m-ms is discussed.
Keywords: ptačí sarkom; Mice; buněčné linie; karyotypizace; Animals; Clone Cells; radiační genetika; buněčné klony; Cell Line; Radiation Genetics; Karyotyping; zvířata; Sarcoma, Avian; myši